Strengthening Alternative Law for Business Dispute Resolution between StateOwned Enterprises and Peace-Oriented Private Enterprises (Benefit-Benefit Solution) - Bambang Hariyanto; Annalisa Yahanan; Muhammad Syaifuddin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The settlement of business disputes in the current State- Owned Enterprises Law accommodates Alternative Dispute Resolution through consensus. However, the ADR regulation only governs disputes between state- owned enterprises and private enterprises. In fact, ADR as a nonlitigation instrument is very suitable and popularly used by business companies at the global and national levels with the principle of beneficial solutions. The absence of ADR provisions for dispute resolution between SOEs and private companies is an issue that has been raised with the following objectives: 1. To analyse the applicable legal provisions on alternative dispute resolution in handling business disputes between SOEs and private companies; 2. Strengthenalternative dispute resolution laws in resolving business disputes between SOEs and private companies with a focus on mutual benefit for the disputing parties (benefit-benefit solution). The results of the study show that: 1. APS regulations are found in different laws and regulations governing various business sectors, but they are not fully and specifically regulated in the State-Owned Enterprise Law, Limited Liability Company Law, Arbitration Law, and the APS itself. 2. Legal reinforcement is needed to regulate ADR in the SOE Law, the PT Law and the establishment of a special ADR Law in order to create peace-oriented ADR that is beneficial to disputing SOEs and BUMS.